Feasibility study on the use of magnetic susceptibility for recovery of vanadium component in magnetite. Issue 5 (2nd November 2022) - Lim, Yoojin; Choi, Jaewoo; Yoo, Kyoungkeun; Lee, Sang-Hun
ABSTRACT: Vanadium in the vanadium-bearing titanomagnetite (VTM) exist by replacing iron in the magnetite crystal, and magnetite should be recovered separately from titanium components in the vanadium-bearing titanomagnetite. In the present study, a sensing system was proposed by measuring magnetic susceptibility of magnetite because the magnetic susceptibility can be easily and quickly measured. The effects of mixing ratio of magnetite and ilmenite with silica and the distance between the magnetic susceptibility meter and the sample bed on the magnetic susceptibility were investigated. The magnetic susceptibility of the mixture of magnetite and ilmenite with 0.1 g or 0.2 g of silica decreased with increasing the ratio of ilmenite in the mixture, but the effect of silica addition was not significant. When the distance between the magnetic susceptibility meter and the sample bed increased, the magnetic susceptibility of magnetite decreased, but the magnetic susceptibility decreased with increasing the thickness of magnetite sample bed of magnetite. Because the magnetic susceptibility depended strongly on the content of magnetite, the sensing system using the magnetic susceptibility measurement could be successfully applied to detect magnetite.